2016
DOI: 10.1016/j.jrmge.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Biological process of soil improvement in civil engineering: A review

Abstract: a b s t r a c tThe concept of using biological process in soil improvement which is known as bio-mediated soil improvement technique has shown greater potential in geotechnical engineering applications in terms of performance and environmental sustainability. This paper presents a review on the soil microorganisms responsible for this process, and factors that affect their metabolic activities and geometric compatibility with the soil particle sizes. Two mechanisms of biomineralization, i.e. biologically contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(67 citation statements)
references
References 40 publications
1
65
0
1
Order By: Relevance
“…Formation of calcite commences when urea decomposes by urease enzyme at a favourable condition, which is normally alkaline in nature. Several studies reported that calcite precipitation occurs most under alkaline condition ranging from 7.5-9.5 [32,33] except for a small group of acid ureases with optimum pH of near neutral [34]. Arunachalam [35] performed MICP treatment using Bacillus sphaericus, a pH of 8 was reported to be the peak for calcite precipitation.…”
Section: Phmentioning
confidence: 99%
“…Formation of calcite commences when urea decomposes by urease enzyme at a favourable condition, which is normally alkaline in nature. Several studies reported that calcite precipitation occurs most under alkaline condition ranging from 7.5-9.5 [32,33] except for a small group of acid ureases with optimum pH of near neutral [34]. Arunachalam [35] performed MICP treatment using Bacillus sphaericus, a pH of 8 was reported to be the peak for calcite precipitation.…”
Section: Phmentioning
confidence: 99%
“…The amount of the CaCO 3 that will be formed during the treatment process depends on the rate of the migration of input materials through the soil texture [29]. The hydrolytic restrictions would be a reason of declination in bacteria activity by restraining bacteria and its products to flow through soil pores [30,31] and interrupts the precipitation process of CaCO 3 . Furthermore, the permeability of the soil can change during the treatment.…”
Section: A Pore Sizementioning
confidence: 99%
“…Are good in solubilizing phosphorus (P) and have the advantage of forming stress-resistant in plants. According to Umar et al (2016), Fusarium enhanced root enlargement. Fusarium also facilitated the development of tap and lateral roots in the plant (Yigit and Dikilitas, 2008) which means for a crop like cassava, Fusarium will facilitate an increase in the number of roots and enlarge root size which are key components of yield determination.…”
Section: Microbes and Soil Improvementmentioning
confidence: 99%